2005
DOI: 10.1369/jhc.4a6500.2005
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine (5HT) Receptors in the Heart Valves of Cynomolgus Monkeys and Sprague-Dawley Rats

Abstract: S U M M A R Y 5-Hydroxytryptamine-2B receptor (5HT2BR) stimulation is known to cause fibroblast mitogenesis, and the mitogenic effect has been proposed to trigger valvular heart disease in humans. In this study, we used real-time polymerase chain reaction (TaqMan) to quantify transcript levels of 5HT2B, 5HT2C, and 5HT1B receptors and immunohistochemistry (IHC) to detect the tissue localization of these receptors in the normal heart valves of cynomolgus (CM) monkeys and Sprague-Dawley (S-D) rats. In both specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 17 publications
1
23
0
3
Order By: Relevance
“…3 Preliminary animal studies using Sprague-Dawley rats and cynomolgus monkeys demonstrated that longterm exposure to high levels of serotonin induces morphological (shortened and thickened aortic cusps and carcinoid like plaques made of myofibroblasts within an ECM of collagen ground substance) as well as echocardiographic changes similar to those seen in human CHD [53][54][55] . It has been demonstrated that the overexpression of 5-HT 2B receptors in hearts of transgenic mice resulted in cardiac hypertrophy and decreased ventricular function due to enhanced ECM deposition and remodelling [56] , whereas genetic deletion of 5-HT 2B receptors has been shown to lead to ventricular dilatation and incomplete cardiac development [57] .…”
Section: Serotonin and Serotonin Receptorsmentioning
confidence: 99%
“…3 Preliminary animal studies using Sprague-Dawley rats and cynomolgus monkeys demonstrated that longterm exposure to high levels of serotonin induces morphological (shortened and thickened aortic cusps and carcinoid like plaques made of myofibroblasts within an ECM of collagen ground substance) as well as echocardiographic changes similar to those seen in human CHD [53][54][55] . It has been demonstrated that the overexpression of 5-HT 2B receptors in hearts of transgenic mice resulted in cardiac hypertrophy and decreased ventricular function due to enhanced ECM deposition and remodelling [56] , whereas genetic deletion of 5-HT 2B receptors has been shown to lead to ventricular dilatation and incomplete cardiac development [57] .…”
Section: Serotonin and Serotonin Receptorsmentioning
confidence: 99%
“…have been demonstrated to be present in heart valve cells 7,9,13 ; thus, the impact of 5-HT on cardiac valve tissue may be both extensive and complex.…”
Section: -Ht Processing Cardiac Valvulopathy and Cardiomyopathymentioning
confidence: 99%
“…The cardiac valvulopathy associated with dexfenfluramine has since been attributed to activation of the 5-HT 2B receptor (Fitzgerald et al, 2000), which unlike the 5-HT 2C subtype is highly localized in cardiac tissue (Elangbam et al, 2005). Because some hallucinogens, such as LSD, are 5-HT 2A receptor agonists, the identification of functionally selective 5-HT 2C agonists is of critical importance and a significant pharmaceutical challenge because of homology within the 5-HT 2 receptor subclass (Nilsson, 2006;Wacker and Miller, 2008).…”
Section: Introductionmentioning
confidence: 99%